John Deere, that's who! - Maurer, Tracy Nelson, 1965- (Henry Holt and Company, 2017)
Back in the 1830s, who was a young blacksmith from Vermont, about to make his mark on American history? John Deere, that's who! Who moved to Illinois, where farmers were struggling to plow through the thick, rich soil they called gumbo? Who tinkered and tweaked and tested until he invented a steel plow that sliced into the prairie easy as you please? Long before the first tractor, who changed farming forever? John Deere, that's who! The life and accomplishments of the blacksmith who invented a steel plow to help till the thick Illinois soil and changed American farming forever.